Antihypertensive Medications Prior to Shock Onset Do Not Impact Initial Vasopressor Requirements in Patients With Shock. (April 2023) - Patel, Jaimini S.; Colon Hidalgo, Daniel; Capistrano, Irene; Mancl, Erin; Rech, Megan A.
Purpose: The effect of the use of antihypertensive agents in patients prior to the development of shock is unclear. The purpose of this study was to determine the impact of antihypertensive agents on vasopressor dose and duration in shock.Materials and Methods: This retrospective, single-center study included patients with shock who received at least one vasopressor for at least 24 hours after shock onset from January 1 to June 30, 2017. Patients taking an antihypertensive agent(s) were compared to those who were not. The primary outcome was the number of vasopressor-free hours at 72 hours. Secondary outcomes included maximum and cumulative vasopressor doses, intensive care unit length of stay, and 30-day mortality.Results: One hundred and sixty-eight patients were included and 99 (59%) were on antihypertensives. Distributive shock was the most common type of shock (75.5%) and more patients taking antihypertensives had hypertension, coronary artery disease, and dyslipidemia at baseline. There was no difference in the number of vasopressor-free hours at 72 hours between patients taking an antihypertensive medication(s) and the control group (2 hours vs 1 hour; P = .11). No difference was found between any of the secondary outcomes.Conclusion: Patients taking antihypertensive agents prior to shock onset did not require increased vasopressor doses or duration.